ENDOSTATIN CONCENTRATION IN PLASMA OF HEALTHY HUMAN VOLUNTEERS - Shah, Inayat; Malik, Muhammad Omar; Khan, Muhammad Jaffar; Fatima, Sadia; Baxendale, Ronald; Habib, Syed Hamid (Journal of Ayub Medical College Abbottabad, 2017)
Background: Angiogenesis is involved in many cardiovascular and cancerous diseases, including atherosclerosis and is controlled by a fine balance between angiogenic and angiostatic mediators. Endostatin is one of the main angiostatic mediators, and inhibits angiogenesis and prevents progression of atherosclerosis. The available literature shows a broad range of concentrations in relatively small samples of healthy controls and is calculated by using different techniques. This study was aimed to determine the basal endostatin concentration in plasma of healthy volunteers, to fully understand its physiological role. Methods: Fifty healthy adult volunteers were recruited to the study. Participants were advised not to participate in any physical activity on the day before the blood sampling. The volunteers' physical activity, height, weight, heart rate and blood pressure were recorded. The samples were analysed for plasma endostatin concentration, using ELISA. The participants were divided by gender and ethnic groups to calculate any difference. Results: Endostatin and other variables were normally distributed. Most of the participants had a moderate level of physical activity with no gender related difference (p=0.370). The mean value for plasma endostatin in all samples was 105±12 ng/ml with range of 81-132 ng/ml. For males, it was 107±13 ng/ml, while for females; 102±12 ng/ml. There were no significant gender or ethnicity related differences in endostatin concentration. Moreover, endostatin was not significantly related with any anthropometric and physical variable. Conclusion: This study gives endostatin levels in normal healthy people and show no gender and ethnicity related differences in endostatin levels. Endostatin was not related with any anthropometric and physical variable. Keywords:Endostatin; Vascular endothelial growth factor; Angiogenesis; Atherosclerosis; Ethnic groups